Saturated Fatty Acids in Obesity-Associated Inflammation - Zhou H; Urso CJ; Jadeja V (Dove Medical Press, 2020)
Heping Zhou, CJ Urso, Viren Jadeja Department of Biological Sciences, Seton Hall University, South Orange, NJ 07079, USACorrespondence: Heping Zhou Email heping.zhou@shu.eduAbstract: Obesity is a major risk factor for the development of various pathological conditions including insulin resistance, diabetes, cardiovascular diseases, and non-alcoholic fatty liver disease (NAFLD). Central to these conditions is obesity-associated chronic low-grade inflammation in many tissues including adipose, liver, muscle, kidney, pancreas, and brain. There is increasing evidence that saturated fatty acids (SFAs) increase the phosphorylation of MAPKs, enhance the activation of transcription factors such as nuclear factor (NF)-κB, and elevate the expression of inflammatory genes. This paper focuses on the mechanisms by which SFAs induce inflammation. SFAs may induce the expression inflammatory genes via different pathways including toll-like receptor (TLR), protein kinase C (PKC), reactive oxygen species (ROS), NOD-like receptors (NLRs), and endoplasmic reticulum (ER) stress. These findings suggest that SFAs act as an important link between obesity and inflammation.Keywords: saturated fatty acids, obesity, inflammation, Toll-like receptor, reactive oxygen species, lipid rafts, protein kinase C